Mr. Murdock - Spain. Embajada (Great Britain)
090/11/1938 034-0086-001 Mr. MURDOCK. A member of the Catering Trade Union of the C.N.T. He went to Spain in May 1936 and joined the C.N.T. Catering Syndicate, because the U.G.T. had no Catering Union at that time. In July 1936 he joined the Republican Army, in the 35th Division. At this time, too, he broke away from the C.N.T. because that body had formed a militia He was wounded in the groin, three bullets being extracted at St. George's Hospital. When he was recovered here he went to the International Brigade, who sent him to the Spanish Embassy. When he saw the latter, they said they would get in contact with Barcelona, but that is a lengthy proceeding. He now wants 15/- as a loan to purchase a waiter's suit. He is confident of securing immediate employment, since his visit to Spain in 1936 was as the result of being one of four waiters on Ministry of Labour exchange labour permits. His address given in the letter from the Spanish Embassy is 220, Arlington Road, Camden Town, N.W. Interviewed Mr Bolton & Mr Gillies 15/- granted 9th November, 1938. 292/946/34/86